Transformation of Cancer Care during and after the COVID Pandemic, a point of no return. The Experience of Italy. (September 2021) - Tarricone, R.; Listorti, E.; Tozzi, V.; Torbica, A.; Banks, H.; Ghislandi, S.; Altini, M.; Annicchiarico, M.; Ardizzoni, A.; Bordon, P.; Bossi, P.; Cascinu, S.; et al.
Highlights: Cancer care planning and delivery must take a comprehensive, nationwide approach to guarantee access to innovation. Digital, community and primary care delivery during the pandemic showed promise in complementing hospital-based care. Leveraging health data analysis and full activation of cancer networks can improve care coordination and address inequalities. Abstract: Policymakers everywhere struggle to introduce therapeutic innovation while controlling costs, a particular challenge for the universal Italian National Healthcare System (SSN), which spends only 8.8% of GDP to care for one of the world's oldest populations. Oncology provides a telling example, where innovation has dramatically improved care and survival, transforming cancer into a chronic condition. However, innovation has also increased therapy duration, adverse event management, and service demand. The SSN risks collapse unless centralized cancer planning changes gear, particularly with Covid-19 causing treatment delays, worsening patient prognosis and straining capacity. In view of the 750 billion Euro "Next Generation EU", released by the European Union to relieve Member States hit by the pandemic, the SSN tapped a multidisciplinary research team to identify key strategies for equitable uptake of innovations in treatment and delivery, with emphasis on data-driven technological and managerial advancements – and lessons from Covid-19.